2011
DOI: 10.2166/wh.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Removal of estrogens and estrogenicity through drinking water treatment

Abstract: Estrogenic compounds have been shown to be present in surface waters, leading to concerns over their possible presence in finished drinking waters. In this work, two in vitro human cell line bioassays for estrogenicity were used to evaluate the removal of estrogens through conventional drinking water treatment using a natural water. Bench-scale studies utilizing chlorine, alum coagulation, ferric chloride coagulation, and powdered activated carbon (PAC) were conducted using Ohio River water spiked with three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
(42 reference statements)
0
5
0
1
Order By: Relevance
“…Several methods for the removal of steroidal oestrogens from water have been explored. Conventional water treatment processes such as coagulation, flocculation, sedimentation, and filtration are not effective for removing EE2 (Johnson et al, 2005;Kuch and Ballschmitter, 2001;Schenck et al, 2012). Thus, the development of new methods for the efficient removal of this pollutant from water bodies is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for the removal of steroidal oestrogens from water have been explored. Conventional water treatment processes such as coagulation, flocculation, sedimentation, and filtration are not effective for removing EE2 (Johnson et al, 2005;Kuch and Ballschmitter, 2001;Schenck et al, 2012). Thus, the development of new methods for the efficient removal of this pollutant from water bodies is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the results suggest there was little or no removal effect following this primary treatment step of the full-scale system. Other studies have reported that chemical precipitation processes using coagulants like aluminum sulfate, which is used at Görvälnverket, result in minimal removal of most endocrine-disrupting compounds (EDCs) [45,50].…”
Section: Discussion On Full-scale Treatment Technologiesmentioning
confidence: 99%
“…It has been reported that PAC is able to remove through adsorption processes a number of EDCs, including E1, E2, EE2, E3 and bisphenol A (Joseph et al, 2013;Schenck et al, 2012;Westerhoff et al, 2005;Yoon et al, 2003). In the past few years, many researchers have demonstrated that AC also has a strong capability of removing a broad range of representative EDCs for artificial and real waste water in the laboratory and pilot and fullscale plants (Choi et al, 2005;Fukuhara et al, 2006;Tsai et al, 2006;Snyder et al, 2007).…”
Section: Estrogenicity (Her-luc)mentioning
confidence: 99%